The Effect of Guiding Services on Ship Visits Queues at PT. Pelabuhan Indonesia II (PERSERO) Tanjung Priok Branch - et. al., Amiruddin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The success of the Port can be seen from the visits of incoming and outgoing ships due to good service to service users. Then PT. Pelabuhan Indonesia II (PERSERO) should make improvements on the basic facilities owned by PT. Pelabuhan Indonesia II (PERSERO) and also plays a very important role in the service of ships is the guidance of ships under the coordination of Scouting Division of PT. Pelabuhan Indonesia II (PERSERO). The success of the service process by PT. Pelabuhan Indonesia II (PERSERO) in supporting the number of ship visits is the faster the ship scouting service, the faster the boat will lean on the dock so that service users benefit from time and costs while the company benefits from the increasing number of vessels served. The pilot operating system and also the addition of guided facilities and infrastructure can allow for a reduction in delays in guide ships to guide ships that have been embanked. The author seeks a solution to the problems that arise in increasing the timeliness of scouting services in reducing delays in guide ships when guiding ships at PT. Pelabuhan Indonesia II (PERSERO). The purpose of conducting this research is to find the relationship and influence of guide services in guiding ships in and out of the port to the number of ship visits at PT. Pelabuhan Indonesia II (PERSERO).